Development and validation of the Epilepsy Surgery Satisfaction Questionnaire (ESSQ‐19). (16th October 2020) - Wiebe, Samuel; Wahby, Sandra; Lawal, Oluwaseyi A.; Sajobi, Tolulope T.; Keezer, Mark R.; Nguyen, Dang K.; Malmgren, Kristina; Tellez‐Zenteno, Jose; Atkinson, Mark J.; Hader, Walter J.; Josephson, Colin B.; Macrodimitris, Sophia; et al.
Abstract: Objective: No validated tools exist to assess satisfaction with epilepsy surgery. We aimed to develop and validate a new measure of patient satisfaction with epilepsy surgery, the 19‐item Epilepsy Surgery Satisfaction Questionnaire (ESSQ‐19). Methods: An initial 31‐item measure was developed based on literature review, patient focus groups, thematic analysis, and Delphi panels. The questionnaire was administered twice, 4‐6 weeks apart, to 229 adults (≥18 years old) who underwent epilepsy surgery ≥1 year earlier, at three centers in Canada and one in Sweden. Participants also completed seven validated questionnaires to assess construct validity. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) assessed the factorial structure of the questionnaire. Cronbach alpha and intraclass correlation coefficients (ICCs) assessed the internal consistency and test‐retest reliability of the ESSQ‐19. Spearman and polyserial correlations assessed construct validity. Results: Median age of participants and time since surgery were 42 years (interquartile range [IQR] = 32‐54) and 5 years (IQR = 2‐8.75), respectively. EFA and CFA yielded 18 items that segregated into four domains (mean score [SD]), namely, seizure control (76.4 [25]), psychosocial functioning (67.3 [26]), surgical complications (84 [22]), and recovery from surgery (73 [24]), one global satisfaction item, and a summary global score (74 [21]). The domain and summary scores demonstrated good to excellent internal reliability (Cronbach ⍺ range = .84‐.95) and test‐retest reliability (ICC range = 0.71‐0.85). Construct validity was supported by predicted correlations with other instruments. Significance: The ESSQ‐19 is a new, valid, and reliable measure of patient satisfaction with epilepsy surgery that can be used in clinical and research settings.